2005
DOI: 10.1103/physrevstab.8.064201
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic description of neutralized drift compression and transverse focusing of intense ion charge bunches

Abstract: A kinetic model based on the Vlasov equation is used to describe the axial drift compression and transverse focusing of an intense ion charge bunch propagating along the axis of a solenoidal focusing field B sol x. The space charge and current of the ion charge bunch are assumed to be completely neutralized by the electrons provided by a dense background plasma. In the absence of self-field forces, the Vlasov equation is solved exactly for general initial distribution function f b x; v; 0, using the method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…We have performed quantitative comparisons of the simulation results with our experimental data, and the agreements with experiments were excellent [12,14]. A three-dimensional kinetic model for longitudinal compression with complete neutralization was developed, and the Vlasov equation was shown to possess a class of exact solutions for the problem [15]. Theories of beam-plasma interaction, with and without external focusing solenoids, have been studied extensively [16][17][18].…”
Section: Longitudinal and Transverse Beam Compressionmentioning
confidence: 69%
See 1 more Smart Citation
“…We have performed quantitative comparisons of the simulation results with our experimental data, and the agreements with experiments were excellent [12,14]. A three-dimensional kinetic model for longitudinal compression with complete neutralization was developed, and the Vlasov equation was shown to possess a class of exact solutions for the problem [15]. Theories of beam-plasma interaction, with and without external focusing solenoids, have been studied extensively [16][17][18].…”
Section: Longitudinal and Transverse Beam Compressionmentioning
confidence: 69%
“…In both the transverse and longitudinal experiments, extensive 3-D simulations, using LSP, were carried out, and the agreement with experiments was excellent [4]. A three-dimensional kinetic model for longitudinal compression was developed, and it was shown that the Vlasov equation possesses a class of exact solutions for the problem [5].…”
Section: Longitudinal and Transverse Beam Compressionmentioning
confidence: 99%
“…The propagation of an intense ion beam pulse through the background plasma has been investigated theoretically through the warm-fluid [15], kinetic [16], hybrid fluid-Vlasov [17], and particle-in-cell simulations [7][8][9]. It is shown that for long, nonrelativistic ion beams, charge neutralization is complete even for very tenuous background plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…III. Finally, for the case of neutralized drift compression, a fully kinetic model based on the Vlasov equation has been developed that describes the longitudinal compression and transverses focusing of an intense ion charge bunch propagating through a background plasma that provides complete charge and current neutralization in a solenoidal magnetic field [39]. + ion charge bunch injected into a 1.4-m -long plasma column, at different times (superimposed).…”
Section: Iid Studies Of Beam Compression and Focusingmentioning
confidence: 99%
“…For fusion energy applications, either un-neutralized [29 -31] or neutralized [32][33][34][35][36][37][38][39] compression may be considered. In the un-neutralized case, to describe the drift compression dynamics and the final focus of the beam particles to a common axial plane and prescribed focal spot size, a warm-fluid model has been employed to describe the longitudinal dynamics of drift compression, coupled nonlinearly to envelope equations that describe the self-consistent transverse dynamics and focusing of the ion beam as it propagates through the quadrupole focusing lattice [30,31].…”
Section: Iid Studies Of Beam Compression and Focusingmentioning
confidence: 99%